Opportunities and advantages of the associative forms in agriculture - Gabriel Ţînţarcu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Setting up of agricultural producers in associative forms open up opportunities for the economic development of their activities, by attracting local or regional advantages and using collective power to increase the prosperity of members, their families and communities they belong to. Associative forms are founded to function on democratic principles valid for all members. The first forms of association in the rural areas in Romania have arose while introducing the modern cooperative principles materialized by Ion Ionescu de la Brad (1818 - 1891), economist, statistician, agronomist, prominent representative of Romanian agricultural sciences and famous politician from that time. The members of associative forms, in any form of organizing they belong to (associations, cooperatives or producers groups), have established democratic rights. Agricultural cooperative is an autonomous association of individuals and / or legal persons, with private legal entity status, established on the freely expressed consent of the parties, to promote the interests of cooperative members. Producer groups can be established for marketing of vegetable, animal, or forestry products. The association is the legal entity consisting of three or more persons, who according to an agreement, put together without the right to return the material contribution, knowledge and their contribution to labor, for the achievement of activities for the public, community, or personal interest.
Keywords: 330; agriculture; associations; cooperatives; producers groups; advantages